RELETIONSHIP TO THE REFLUXATE TYPE OF THE EFFECTIVENESS OF TREATMENT DEGREE OF GASTROESOPHAGEAL REFLUX DISEASE (World Bulletin of Public Health, 2024)
All measurements drawn at every level of AT treatment method of GERD are dedicated to logically enable the gastroesophageal reflux or duodenogastroezophageal reflux process, which does the function of generator at the occurance of this disease. Even the scope of medicine (mainly prokinetics which are used individually) used at the medicamental level of alternative treatment method is small, it was defined that its therapeutical efficiency level can completely compete with the same indications of traditional method.
Keywords: gastroesophageal reflux disease; possible to conclude